Why nations go to war - Stoessinger, John George (Belmont, CA : Thomson/Wadsworth, 2005)
This book is intended for International Relations, World Politics, Global Issues and History courses that deal with issues of war and peace.
The Iron Dice: World War I -- Barbarossa: Hitler's attack on Russia -- The Temptations of victory: Korea -- A Greek tragedy in five acts: Vietnam -- From Sarajevo to Kosovo: The war over the remains of Yugoslavia -- Four battles over God: India and Pakistan in 1947, 1965, 1971, and 1998 -- The Fifty Years' War in the Holy Land: Israel and the Arabs -- Saddam Hussein's wars against Iran and Kuwait -- New wars for a new century: America and the world of Islam -- Why nations go to war.
Includes bibliographical references and index.
Keywords: 1900-1999; History, Modern -- 20th century; War; wars; armed conflicts; History, Modern; War; Oorlog; Oorzaken